Assessing the Passenger Load of Urban Bus Performance in Eastern Region Malaysia Peninsular - Bakar M.F.A.; Ismail N.; Norhisham S.; Ahad N.A.; Okwonu F.Z.; Nor S.E.M.; Azlan N.N.I.M.; Zaini N.A.; Dullah H. (Springer Science and Business Media Deutschland GmbH, 2024)
Public transport should improve availability and versatility and capable to reduce the dependency on private vehicle at once. The statistics shows that in 2020 recorded more than 32.30 million of active vehicle in this country, and these numbers were increased by 3.73% from previous years. The aim of this study is to conduct the assessment on the passenger load of urban bus performance in eastern region of Malaysian Peninsular which comprised of Kelantan, Terengganu, and Pahang. Transit Capacity and Quality of Service of Manual (TCPRM) have referred as a guideline in this study. The overall of mean QOS of passenger load for these three capital states was categorized as QOS A. These several routes recorded a significant number of passengers in this study. It shows that Route 4 in Kota Bahru achieved highest average of passenger load. Unfortunately, the amount of the passenger utilized the public bus services in this region still consider lower than another region of Malaysia Peninsular. Authority should focus on promoting bus services a main transportation since bus services the only public transportation in location. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.